(untitled) (Research, Society and Development, 2022)
COVID-19 is an infectious disease caused by the SARS-CoV-2 coronavirus and is capable of affecting different people in different ways. Despite its well-known symptoms and causative agents, its deleterious effects are still considered a mystery, both in terms of its causes and its duration. One of the effects that have caught the attention of scientists is hair loss. The main objective of this work is based on investigating and understanding the relationship between hair loss and a COVID-19, as well as on the most suitable processes for this. In order to achieve the objective, an integrative qualitative and descriptive review was applied, considering the search terms ("COVID-19" [DeCS]) OR ("coronavirus" [DeCS]) AND ("hair loss" ”[DeCS]) on the Publish or Perish platform. The research was carried out on December 8, 2021 and used as bases: Google scholar, PubMed, and Lilacs. Although there is no scientific evidence of a direct relationship between COVID-19 and hair loss, studies demonstrate the existence of an indirect relationship. Symptoms of COVID-19, such as fever and stress (among other psychosocial changes) are considered to enhance the fall, as well as responses to medications used to cure COVID-19. Regarding the treatment, although there are some studies on some medications that are more effective than others, the best option is to seek a specialist, so that the treatment can be assertive and individual.